Sleep problems and social support: Frailty in a Brazilian Elderly Multicenter Study Problemas de sueño y soporte social: estudio multicéntrico sobre Fragilidad en Ancianos Brasileños Problemas de sono e suporte social: estudo multicêntrico Fragilidade em Idosos Brasileiros - Shintia Viana da Costa; Maria Filomena Ceolim; Anita Liberalesso Neri (Universidade de São Paulo, 2011)
This study identifies relationships among the quality of perceived social support and sleep problems and napping habits in community-dwelling elderly. This study is part of a larger multicenter project entitled "Frailty in Brazilian Elderly Individuals", conducted in 17 Brazilian cities. A total of 498 elderly individuals capable of participating in interviews and free of cognitive deficits or functional impairment were found. The following instruments were used in data collection: Questionnaire addressing socio-demographic data; Interpersonal Support Evaluation Scale; questions concerning sleep patterns (Nottingham Health Profile); questions related to napping habits (Minnesota Leisure Activity Questionnaire). Descriptive statistics and the Mann-Whitney test were used for data analysis. The elderly individuals who reported having sleep problems in general, taking longer to fall asleep and sleeping poorly at night had lower scores on the Interpersonal Support Evaluation Scale than the elderly who denied such problems. Strategies to improve the quality of social support could also help reduce sleep problems. Este artículo tiene como objetivo identificar relaciones entre calidad del soporte social percibido, problemas de sueño y hábito de dormitar, en ancianos de la comunidad. Se trata de un recorte del estudio Fragilidad en Ancianos Brasileiros (FIBRA), proyecto multicéntrico desarrollado en 17 ciudades brasileñas. Participaron 498 ancianos, capaces de responder a las entrevistas, sin déficit cognitivo o funcional grave. Se adoptó para la recolección de datos: el Cuestionario Sociodemográfico; la Escala de Percepción de la Calidad del Soporte Social; preguntas sobre problemas de sueño (Perfil de Salud de Nottingham); y, preguntas sobre el hábito de dormitar (Minnesota Leisure Activity Questionnaire). Se utilizó estadística descriptiva y prueba de Mann-Whitney para tratamiento de los datos. Los ancianos que refirieron problemas de sueño en general, demorar en adormecer y dormir mal en la noche, presentaron puntajes inferiores a los de ancianos que negaban esos problemas, en la Escala de Percepción de Calidad de Soporte Social. Las estrategias para mejorar la calidad de soporte social podrían contribuir para minimizar los problemas de sueño. Esta pesquisa teve como objetivo identificar relações entre qualidade do suporte social percebido, problemas de sono e hábito de cochilar, em idosos da comunidade. Trata-se de recorte do estudo Fragilidade em Idosos Brasileiros (Fibra), projeto multicêntrico, desenvolvido em 17 cidades brasileiras. Participaram 498 idosos, capazes de responder às entrevistas, sem déficit cognitivo ou funcional grave. Adotou-se, para coleta de dados: questionário sociodemográfico, escala de percepção da qualidade do suporte social, questões sobre problemas de sono (perfil de saúde de Nottingham); questões sobre hábito de cochilar (Minnesota Leisure Activity Questionnaire). Utilizou-se estatística descritiva e teste de Mann-Whitney para tratamento dos dados. Idosos que referiram problemas de sono em geral, demorar para adormecer e dormir mal à noite apresentaram escores inferiores aos dos idosos que negavam esses problemas, na escala de percepção de qualidade de suporte social. Estratégias para melhoria da qualidade de suporte social poderiam contribuir para minimizar problemas de sono.